Strategies and Media for Enhancing Writing Skills Among ELT Students: A Systematic Literature Review - Mohammad Irvan; Erlik Widiyani Styati (Universitas PGRI Madiun, 2025)
This systematic literature review examines strategies and media used to enhance writing skills among ELT students in EFL contexts. The review systematically analyzes four key pedagogical strategiesgraphic organizers, translanguaging, writing process approach, and pair workand four types of instructional mediadigital photographs, Google Classroom, YouTube videos, and fantasy movies. Drawing from classroom-based experiments, quasi-experimental studies, and descriptive research, findings demonstrate that these interventions significantly improve students' content development, text organization, vocabulary precision, mechanical accuracy, motivation, and classroom engagement. Graphic organizers and process writing provide cognitive scaffolding for idea generation and structuring, while translanguaging and pair work support linguistic and social dimensions of writing development. Digital media deliver authentic multimodal input that enriches writing tasks and fosters digital literacy. However, implementation challenges persist, including students' confidence in target language production, technological access limitations, and digital equity concerns, particularly in post-pandemic educational settings. Compared with broader ELT research trends, the findings underscore the necessity of principled integration between cognitive strategies, collaborative practices, and technology-enhanced media for optimal writing instruction. The review offers practical implications for ELT curriculum design, teacher professional development, and technology implementation strategies, alongside recommendations for future research including longitudinal studies of strategy-media combinations and investigations across diverse educational contexts.